Cutaneous manifestations and dermatological sequelae of Covid‐19 infection compared to those from other viruses. (17th February 2021) - Sharma, Surabhi; Raby, Edward; Prasad Kumarasinghe, Sujith
Abstract: In the last few months, there have been numerous reports describing a variety of cutaneous signs associated with COVID‐19. Clinicians from Italy were the first to describe the cutaneous manifestations of COVID‐19, which were later observed in other parts of the globe. In some cases, cutaneous signs were the only manifestation of COVID‐19 rather than the typical syndrome of fever and upper respiratory tract symptoms. However, there is considerable heterogeneity amongst the cutaneous signs described so far, which has been published extensively. Our aim is to summarise the latest studies that have reported the early and late cutaneous signs of COVID‐19 and compare them to the most common established viral exanthems.